2018
DOI: 10.2147/copd.s152574
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic COPD patients and NIV at home: is there any benefit? Using the CAT and BODE index in an effort to prove benefits of NIV in these patients

Abstract: IntroductionThe benefits of long-term noninvasive ventilation (NIV) in stable COPD with chronic hypercapnic respiratory failure (CHRF) have been debated for many years due to the conflicting results observed in these patients.Materials and methodsWe investigated the effects of domiciliary NIV in stable hypercapnic COPD patients for a period of 1 year using COPD Assessment Test (CAT), BODE Index, and the number of acute exacerbations. NIV was administered in 57 stable COPD patients with CHRF in the spontaneous/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This overall improved performance was accompanied by concordant spirometric function parameters that are congruent with other published data. Zikyri found a comparable improvement in FVC after initial initiation of outpatient NIV [4]. Nevertheless, the changes in lung function are on average only minor and do not reflect the clear differences in the 6MWT.…”
Section: Plos Onementioning
confidence: 88%
See 1 more Smart Citation
“…This overall improved performance was accompanied by concordant spirometric function parameters that are congruent with other published data. Zikyri found a comparable improvement in FVC after initial initiation of outpatient NIV [4]. Nevertheless, the changes in lung function are on average only minor and do not reflect the clear differences in the 6MWT.…”
Section: Plos Onementioning
confidence: 88%
“…After non-invasive ventilation (NIV) was established in the 1980s for acute ventilatory failure, it is now also recommended as a long-term treatment for patients with stable chronic obstructive pulmonary diseases (COPD) and concomitant chronic hypercapnia in an outpatient setting [1]. This is based on numerous studies that demonstrated an improvement in the quality of life of patients with advanced COPD and stable hypercapnic respiratory failure [2][3][4][5][6]. In these patients, mortality rates can be reduced when high ventilation pressure is applied and a significant reduction in arterial pCO 2 is achieved [7].…”
Section: Introductionmentioning
confidence: 99%
“…Severe COPD patients with GOLD III and IV will develop CHRF [ 18 ], which provokes more often exacerbations, shown to be a poor prognostic factor for survival [ 5 , 14 , 19 ]. Ventilation-perfusion inequality always causes an increased arterial PaCO 2 or hypercapnia in COPD patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with the literature, which implicated the association of PaCO 2 and poor outcomes of COPD. Zikyri et al [ 5 ] reported that domiciliary NIV reduced the levels of PaCO 2 of stable COPD patients with CHRF with a significant improvement in the BODE index. NIV can not only alleviate the airway wall edema to improve the lung function but also relieve fatiguing respiratory muscles by reducing degree of hyperinflation to provide patients a better exercise capacity [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation